About Theory of Giving of an Immovable Thing - Yu. V. Baygusheva (Теоретическая и прикладная юриспруденция)
The author qualifies the giving of an immovable thing as a type of disposition transactions and the author contrasts the giving and the basic obligatory contract. The article analyzes the factual composition of the giving-contract, concludes about the abstract nature of this contract.